2018
DOI: 10.1186/s12886-018-0679-4
|View full text |Cite
|
Sign up to set email alerts
|

Does rituximab improve clinical outcomes of patients with thyroid-associated ophthalmopathy? A systematic review and meta-analysis

Abstract: BackgroundThe current therapies of thyroid-associated ophthalmopathy (TAO) were still a challenging matter. In this study, we aimed to contrast the impact of before- after rituximab (RTX) therapy in the patients with TAO.MethodsWe searched the PubMed, EMBASE, and SCOPUS databases for articles published up to July 3, 2017. Fixed- or random-effects meta-analysis was used to provide pooled estimates of standard mean difference (SMD) both the primary outcome from clinical activity score (CAS), and secondary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Next, B cells returning after depletion secreted reduced levels of interleukin-6 in humans [ 113 ]. However, interleukin-6 serum levels were shown to be unaffected six months after B cell depletion [ 114 ].…”
Section: Effects Of Ms Medications On Peripheral B Cells In Humansmentioning
confidence: 99%
“…Next, B cells returning after depletion secreted reduced levels of interleukin-6 in humans [ 113 ]. However, interleukin-6 serum levels were shown to be unaffected six months after B cell depletion [ 114 ].…”
Section: Effects Of Ms Medications On Peripheral B Cells In Humansmentioning
confidence: 99%
“…However, our studies showed some positive association of aequorin TSAb and the effect of pulse therapy on different orbital findings. We, therefore, emphasized the clinical usefulness of this new assay and the importance of prospective monitoring during conventional treatment or new pharmacological treatments for GO [19,20]. Further prospective studies are indicated to clarify the use-fulness of this assay to assess the occurrence or progression of ophthalmopathy.…”
Section: Discussionmentioning
confidence: 98%
“…In SLE and rheumatoid arthritis patients, BAFF levels were found to be elevated during B-cell depletion and declined upon B-cell repopulation [ 131 , 132 ]. B cells returning after depletion secreted reduced levels of IL-6 in humans and IL-6 serum levels were shown to be unaffected six months after B cell depletion [ 22 , 133 ]. Further, the depletion of regulatory B cells was associated with an enhanced secretion of pro-inflammatory cytokines by CD11b + antigen-presenting cells [ 134 ].…”
Section: Current and Evolving Therapeutic Strategies In Nmosdmentioning
confidence: 99%